Measurement of the transverse momentum and [phi]∗[eta] distributions of Drell-Yan lepton pairs in proton–proton collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2016)
Distributions of transverse momentum pℓℓT and the related angular variable ϕ∗η of DrellΓÇôYan lepton pairs are measured in 20.3┬áfb−1 of protonΓÇôproton collisions at s√=8┬áTeV with the ATLAS detector at the LHC. Measurements in electron-pair and muon-pair final states are corrected for detector effects and combined. Compared to previous measurements in protonΓÇôproton collisions at s√=7┬áTeV, these new measurements benefit from a larger data sample and improved control of systematic uncertainties. Measurements are performed in bins of lepton-pair mass above, around and below the Z-boson mass peak. The data are compared to predictions from perturbative and resummed QCD calculations. For values of ϕ∗η<1 the predictions from the Monte Carlo generator ResBos are generally consistent with the data within the theoretical uncertainties. However, at larger values of ϕ∗η this is not the case. Monte Carlo generators based on the parton-shower approach are unable to describe the data over the full range of pℓℓT while the fixed-order prediction of Dynnlo falls below the data at high values of pℓℓT. ResBos and the parton-shower Monte Carlo generators provide a much better description of the evolution of the ϕ∗η and pℓℓT distributions as a function of lepton-pair mass and rapidity than the basic shape of the data.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und sehr viele weitere Personen]
Im Titel sind [phi] und [eta] als griechische Buchstaben dargestellt
Im Titel ist das Zeichen "∗" hochgestellt
Im Titel ist [eta] tiefgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol